Geometric Progression : Problems and Solutions -Part (2)
Exercises
- If $x, y, z$ are in G.P., prove that $\log x, \log y, \log z$ are in A.P.
- If the $n^{\text {th }}$ term of the G.P. $5,10,20, \ldots$ is equal to the $n^{\text {th }}$
term of the G.P. $1280,640,320, \ldots$, find the value of $n$. - Find three numbers in G.P. whose sum is 19 and whose product is $216 .$
- If in a GP the $(p+q)^{\text {th }}$ term is $a$ and the $(p-q)^{\text {th }}$ term is $b$,
prove that the $p^{\text {th }}$ term is $\sqrt{a b}$.
Solution $x, y, z$ ane in G.P.
$\begin{aligned}
&\\
\therefore \dfrac{y}{x}&=\dfrac{z}{y} \\\\
\log \left(\dfrac{y}{x}\right)&=\log \left(\dfrac{z}{y}\right) \\\\
\log y-\log x&=\log z-\log y\\\\
\end{aligned}$
$\therefore \quad \log x, \log y, \log z$ are in A.P.
SOLUTION $\begin{aligned}
5,10,20, \ldots \text { is a G.P. }& \\\\
a &=5 \\\\
r &=\dfrac{10}{5}=2 . \\\\
u_{n} &=a r^{n-1} \\\\
&=5(2)^{n-1} \\\\
1280,640,320, \ldots \text { is a G.P. } \\\\
a &=1280 \\\\
r &=\dfrac{640}{1280}=\dfrac{1}{2}\\\\
u_{n} &=a r^{n-1} \\\\
&=1280\left(\dfrac{1}{2}\right)^{n-1} \\\\
&=1280(2)^{1-n}\\\\
\text{By the problem,}&\\\\
5(2)^{n-1} &=1280(2)^{1-n} \\\\
\therefore \dfrac{2^{n-1}}{2^{1-n}} &=256 \\\\
2^{2 n-2} &=2^{8} \\\\
2 n-2 &=8 \\\\
2 n &=10 \\\\
n &=5
\end{aligned}$
SOLUTION Let the three numbers in GP be $a$, ar, $a r^{2}\\\\$.
By the problem,
$\begin{aligned}
&\\
a+a r+a r^{2}&=19 \\\\
a\left(1+r+r^{2}\right)&=19\dots(1)\\\\
a\cdot ar\cdot a r^{2} &=216 \\\\
a^{3} r^{3} &=6^{3} \\\\
(a r)^{3} &=6^{3}\\\\
ar &=6\\\\
a&=\dfrac{6}{r}\dots(2)\\\\
\end{aligned}$
Substituting $a=\dfrac{6}{r}$ in equation (1),
$\begin{aligned}
&\\
\dfrac{6}{r}\left(1+r+r^{2}\right)&=19\\\\
6+6 r+6 r^{2}&=19 r\\\\
6 r^{2}-13 r+6&=0\\\\
(3 r-2)(2 r-3)&=0\\\\
r=\dfrac{2}{3} \text{ or } r=\dfrac{3}{2}\\\\
\text{When } r=\dfrac{3}{2},&\\\\
a=\dfrac{6}{3 / 2}&=4\\\\
\therefore\ 1^{\text{st}} \text { number } &= 4\\\\
2^{\text{nd}} \text { number } &= 6\\\\
3^{\text{rd}} \text { number } &= 9\\\\
\text{When } r=\dfrac{2}{3},&\\\\
a=\dfrac{6}{2 / 3}&=9\\\\
\therefore\ 1^{\text{st}} \text { number } &= 9\\\\
2^{\text{nd}} \text { number } &= 6\\\\
3^{\text{rd}} \text { number } &= 4\\\\
\end{aligned}$
Solution
Let the first term and the common ratio of given G.P.
be $A$ and $R$ respectively.
By the problem,
$\begin{aligned}
&\\
u_{p+q}&=a \\\\
A R^{p+q-1}&=a\ldots(1) \\\\
u_{p-q}&=b\\\\
A R^{p-q-1} &=b \ldots(2)\\\\
\text { Miltiply equation (1) } & \text { by equation (2), }\\\\
A R^{p+q-1} \cdot A R^{p-q-1} &=a b \\\\
A^{2} R^{2 p-2} &=a b \\\\
\left(A R^{p-1}\right)^{2} &=a b \\\\
A R^{p-1} &=\sqrt{a b} \\\\
\therefore\ u_p &=\sqrt{a b}
\end{aligned}$
the reciprocal of the third. Which term of this GP is unity?
SOlUTION
$\begin{aligned}
\text { In a G.P., }& \\\\
u_{3}&=6 \dfrac{1}{4} \\\\
a r^{2}&=\dfrac{25}{4}\ldots(1) \\\\
u_{7}&=\dfrac{4}{25} \\\\
a r^{6}&=\dfrac{4}{25}\ldots(2)\\\\
\therefore \dfrac{a r^{6}}{a r^{2}} &=\dfrac{\frac{4}{25}}{\frac{25}{4}} \\\\
r^{4} &=\dfrac{16}{625} \\\\
r &=\dfrac{2}{5} \\\\
\therefore\ a\left(\dfrac{2}{5}\right)^{2} &=\dfrac{25}{4} \\\\
\dfrac{4 a}{25} &=\dfrac{25}{4}\\\\
\therefore\ a &=\dfrac{625}{16} \\\\
\therefore\ a r^{4} &=\dfrac{625}{16} \times \dfrac{16}{625} \\\\
\therefore\ u_{5} &=1
\end{aligned}$
prove that $x, y, z$ are the three consecutive terms of a G.P.
SOLUTION
$\dfrac{1}{x+y},\ \dfrac{1}{2 y},\ \dfrac{1}{y+z}$ are in A.P.
$\begin{aligned}
&\\
\dfrac{1}{2 y}-\dfrac{1}{x+y}&=\dfrac{1}{y+z}-\dfrac{1}{2 y} \\\\
\dfrac{x+y-2 y}{2 y(x+y)}&=\dfrac{2 y-y-z}{2 y(y+z)} \\\\
\dfrac{x-y}{2 y(x+y)}&=\dfrac{y-z}{2 y(y+z)} \\\\
\dfrac{x-y}{x+y}&=\dfrac{y-z}{y+z} \\\\
(x-y)(y+z)&=(x+y)(y-z) \\\\
x y-y^{2}+x z-y z&=x y+y^{2}-x z-y z \\\\
x z-y z+x z+y z&=2 y^{2} \\\\
2 x z&=2 y^{2} \\\\
y^{2}&=x z\\\\
\therefore\ \dfrac{y}{x}&=\dfrac{z}{y}\\\\
\end{aligned}$
Hence, $x,\ y,\ z$ are in G.P.
$a, b, c$ are in G.P., prove that $\dfrac{a}{x}+\dfrac{c}{y}=2$.
SOLUTION
A.M between $a$ and $b=x\\\\$
$\dfrac{a+b}{2}=x\\\\$
A.M between $b$ and $c=y\\\\$
$\dfrac{b+c}{2}=y\\\\$
$a, b, c$ are in a G.P. $\\ $
$\dfrac{b}{a}=\dfrac{c}{b} \Rightarrow b^{2}=a c$
$\begin{aligned}
&\\
& \dfrac{a}{x}+\dfrac{c}{y} \\\\
=& \dfrac{a}{\dfrac{a+b}{2}}+\dfrac{c}{\dfrac{b+c}{2}} \\\\
=& \dfrac{2 a}{a+b}+\dfrac{2 c}{b+c} \\\\
=& \dfrac{2(a b+a c+a c+b c)}{a b+a c+b^{2}+b c} \\\\
=& \dfrac{2\left(a b+2 b^{2}+b c\right)}{a b+2 b^{2}+b c}\left(\because b^{2}=a c\right) \\\\
=& 2
\end{aligned}$
find the two numbers
SOLUTION
Let the two numbers be $a$ and $b\\\\ $.
A.M between $a$ and $b=30\\\\ $
$\begin{aligned}
\dfrac{a+b}{2} &=30 \\\\
a+b &=60 \\\\
b &=60-a\\\\
\end{aligned}$
G.M. between $a$ and $b=18\\\\ $
$\begin{aligned}
\sqrt{a b}&=18\\\\
a b &=324 \\\\
a(60-a) &=324 \\\\
60 a-a^{2} &=324 \\\\
a^{2}-60 a+32 y &=0 \\\\
(a-6)(a-54) &=0 \\\\
a=6 \text { or } a &=54\\\\
\end{aligned}$
When $a=6, b=60-6=54\\\\ $.
When $a=54, b=60-54=6\\\\ $.
$\therefore$ The two numbers are $6$ and $54$.
If $2, a, b$ are in A.P. and $b, c, 18$ are in G.P., then find $c$.
SOLUTION
$2, a, b$ are in A.P.
$\begin{aligned}
&\\
\therefore a &=\dfrac{2+b}{2} \\\\
&=1+\dfrac{b}{2}\\\\
\end{aligned}$
$b, c, 18$ are in G.P.
$\begin{aligned}
&\\
\dfrac{c}{b} &=\dfrac{18}{c} \\\\
\therefore b &=\dfrac{c^{2}}{18} \\\\
\therefore a &=1+\dfrac{c^{2}}{36} \cdot \\\\
a+b+c &=25 \text { (given) }\\\\
1+\dfrac{c^{2}}{36}+\dfrac{c^{2}}{18}+c &=24 \\\\
\dfrac{3 c^{2}}{36}+c &=24 \\\\
\dfrac{c^{2}}{12}+c &=24 \\\\
c^{2}+12 c-288 &=0 \\\\
(c+24)(c-12) &=0 \\\\
c=-24\ \text { or }\ c &=12\\\\
\end{aligned}$
Since $2 < c < 18, c=-24$ is impossible.
$\begin{aligned}
&\\
&\therefore\ c=12
\end{aligned}$
If the $3^{\text {rd }}, 4^{\text {th }}$ and $7^{\text {th }}$ terms of this A.P.
are the first three terms of a G.P., show that $a=-\dfrac{3}{2} d$.
Hence show that the $4^{\text {th }}$ term of the G.P. is
the $16^{\text {th }}$ term of the A.P.
SOlution
In an A.P.,
$\begin{aligned}
&\\
a&=\text { first term } \\\\
d&=\text { common difference } \\\\
u_{3}&=a+2 d \\\\
u_{4}&=a+3 d \\\\
u_{7}&=a+6 d \\\\
\end{aligned}$
By the problem,
$a+2 d, a+3 d, a+6 d$ are in a G.P.
$\begin{aligned}
&\\
\therefore \dfrac{a+3 d}{a+2 d} &=\dfrac{a+6 d}{a+3 d} \\\\
\therefore a^{2}+6 a d+9 d^{2} &=a^{2}+8 a d+12 d^{2} \\\\
\therefore \quad-2 a d &=3 d^{2} \\\\
a &=-\dfrac{3}{2} d\\\\
\end{aligned}$
Let the common ratio of G.P. be $r$.
$\begin{aligned}
&\\
\text { then, } r &=\dfrac{a+3 d}{a+2 d} \\\\
&=\dfrac{-\dfrac{3}{2} d+3 d}{-\dfrac{3}{2} d+2 d} \\\\
&=3 \\\\
\therefore\ 4^{\text {th }} \text { term of G.P.} &=3(a+6 d) \\\\
&=3\left(-\dfrac{3}{2} d+6 d\right) \\\\
&=\dfrac{27}{2} d\\\\
16^{\text {th }} \text { term of A.P. } &=a+15 d \\\\
&=-\dfrac{3}{2} d+15 d \\\\
&=\dfrac{27}{2} d\\\\
\end{aligned}$
Hence, proved.
with a common difference 6 . If the first number is the same as the $4^{\text {th }}$,
find the four numbers.
SOLUTION
Let $A=\{w, x, y, z\}\\\\$
By the problem,
$w, x, y$ are in GP.
$\\ \dfrac{x}{w}=\dfrac{y}{x}\\\\$
$x, y, z$ are in A.P.
Let the common difference be $d.\\\\$
$\begin{aligned}
\therefore\ x &=x, y=x+6, z=x+12 \\\\
w &=z(\text { given }) \\\\
\therefore\ w &=x+12 \\\\
\dfrac{x}{x+12} &=\dfrac{x+6}{x} \\\\
x^{2} &=x^{2}+18 x+72 \\\\
x &=-4 \\\\
\therefore\ y &=2, z=w=8
\end{aligned}$
between them, prove that $a: b=\left(2+\sqrt{3}\right): \left(2-\sqrt{3}\right)$
SOLUTION
A.M. between $a$ and $b=\dfrac{a+b}{2}\\\\ $
G.M. between $a$ and $b =\sqrt{a b} \\\\ $
$\begin{aligned}
\text{By the problem} &\\\\
\text{A.M.} &= 2\cdot\text {G.M.}\\\\
\dfrac{a+b}{2}&=2 \sqrt{a b} \\\\
a+b&=4 \sqrt{a b} \\\\
(a+b)^{2}&=16 a b \dots(1)\\\\
a^{2}+2 a b+b^{2}&=16 a b \\\\
a^{2}-14 a b+b^{2}&=0\\\\
a^{2}-2 a b+b^{2}&=12 a b \\\\
(a-b)^{2}&=12 a b\ldots(2) \\\\
\text{By } (1)\div (2), &\\\\
\dfrac{(a+b)^{2}}{(a-b)^{2}}&=\dfrac{16 a b}{12 a b} \\\\
\left(\dfrac{a+b}{a-b}\right)^{2}&=\dfrac{4}{3}\\\\
\dfrac{a+b}{a-b}&=\dfrac{2}{\sqrt{3}} \\\\
2 a-2 b&=\sqrt{3} a+\sqrt{3} b \\\\
2 a-\sqrt{3} a&=2 b+\sqrt{3} b \\\\
a(2-\sqrt{3})&=b(2+\sqrt{3}) \\\\
\therefore \dfrac{a}{b}&=\dfrac{2+\sqrt{3}}{2-\sqrt{3}}
\end{aligned}$
$G_{1}, G_{2}$ are two G.M.s between the same two numbers, then prove that
$\dfrac{A_{1}+A_{2}}{G_{1} G_{2}}=\dfrac{a+b}{a b}$.
SOLUTION
$A_{1}, A_{2}$ are the two A.M.s between two numbers $a$ and $b\\\\ $
$\therefore a, A_{1}, A_{2}, b$ is an A.P.
$\begin{aligned}
&\\
\therefore \quad A_{1}-a &=b_{-} A_{2} \\\\
A_{1}+A_{2} &=a+b \\\\
\end{aligned}$
$G_{1}, G_{2}$ are the two G.M.s between $a$ and $b.\\\\ $
$a, G_{1}, G_{2}, b$ is a G.P.
$\begin{aligned}
\dfrac{G_{1}}{a} &=\dfrac{b}{G_{2}} \\\\
G_{1} G_{2} &=a b . \\\\
\therefore \dfrac{A_{1}+A_{2}}{G_{1} G_{2}} &=\dfrac{a+b}{a b}
\end{aligned}$
Prove that the numbers are $A \pm \sqrt{A^{2}-G^{2}}$
SOLUTION
$\begin{aligned}
\therefore\ \dfrac{a+b}{2} &=A \\\\
a+b &=2 A \\\\
\sqrt{a b} &=G \\\\
a b &=G^{2} \\\\
\left(a+b^{2}\right) &=4 A^{2} \\\\
a^{2}+2 a b+b^{2} &=4 A^{2}\\\\
a^{2}+b^{2} &=4 A^{2}-2 a b \\\\
a^{2}+b^{2}-2 a b &=4 A^{2}-4 a b \\\\
(a-b)^{2} &=4 A^{2}-4 G^{2} \\\\
a-b &=2 \sqrt{A^{2}-G^{2}} \\\\
\text{By } (1)+(2), & \\\\
2 a &=2 A+\sqrt{A^{2}-G^{2}} \\\\
\therefore\ a &=A+\sqrt{A^{2}-G^{2}} \\\\
\text{By } (1)-(2),\\\\
2b &=2 A-2 \sqrt{A^{2}-G^{2}} \\\\
\therefore\ b &=A-\sqrt{A^{2}-G^{2}}
\end{aligned}$
then prove that the numbers are in the ratio $\left(m+\sqrt{m^{2}-n^{2}}\right):\left(m-\sqrt{m^{2}-n^{2}}\right)$.
SOLUTION
Let the two numbers be $a$ and $b\\\\ $.
A.M. between $a$ and $b=\dfrac{a+b}{2}\\\\ $
G.M. between $a$ and $b=\sqrt{a b}\\\\ $
By the problem,
$\begin{aligned}
&\\
\dfrac{\text{A.M}}{\text{G.M}}&=\dfrac{m}{n} \\\\
\dfrac{a+b}{2 \sqrt{a b}}&=\dfrac{m}{n}\\\\
\text{Let } a+b=k m, 2 \sqrt{a b}&=k n\\\\
\therefore\ (a+b)^{2} &=k^{2} m^{2} \\\\
4 a b &=k^{2} n^{2} \\\\
a^{2}+2 a b+b^{2} &=k^{2} m^{2} \\\\
a^{2}+2 a b+b^{2}-4 a b &= k^{2} n^{2}-4 a b \\\\
a^{2}-2 a b+b^{2} &=k^{2} m^{2}-k^{2} n^{2} \\\\
(a-b)^{2} &=k^{2}\left(n^{2}-n^{2}\right) \\\\
a-b &=k \sqrt{m^{2}-n^{2}}\\\\
\dfrac{a+b}{a-b} &=\dfrac{k m}{k \sqrt{m^{2}-n^{2}}} \\\\
&=\dfrac{m}{\sqrt{m^{2}-n^{2}}}\\\\
\end{aligned}$
By Componendo and Dividendo,
$\begin{aligned}
&\\
\dfrac{(a+b)+(a-b)}{(a+b)-(a-b)} &=\dfrac{m+\sqrt{m^{2}-n^{2}}}{m-\sqrt{m^{2}-n^{2}}} \\\\
\dfrac{2 a}{2 b} &=\dfrac{m+\sqrt{m^{2}-n^{2}}}{m-\sqrt{m^{2}-n^{2}}} \\\\
\dfrac{a}{b} &=\dfrac{m+\sqrt{m^{2}-n^{2}}}{m-\sqrt{m^{2}-n^{2}}}
\end{aligned}$
$\begin{aligned}
x+y+z &=a+4 \\\\
2 x-y+2 z &=2 a+2 \\\\
3 x+2 y-3 z &=1-2 a\\\\
\end{aligned}$
where $x, y, z$ in this order are in G.P. and $a$ is a positive real number.
Find the value of $a$.
SOLUTION
$\begin{aligned}
x+y+z=a+4 \ldots(1)&\\\\
2 x-y+2 z=2 a+2 \ldots(2)&\\\\
3 x+2 y-3 z=1-2 a\ldots(3)& \\\\
\text{By } (1)+(2),& \\\\
3 x+3 z =3 a+6 &\\\\
\therefore\ x+z =a+2& \\\\
\text { Substituting } x+z=a+2 &\text { in (1) } \\\\
a+2+y&=a+4 \\\\
\therefore\ y&=2\\\\
(2) \times 2 \Rightarrow\ 4 x-2 y+4 z&=4 a+4 \\\\
(3) \times 1 \Rightarrow\ 3 x+2 y-3 z&=1-2 a \\\\
\text { By addition, } 7 x+z&=2 a+5 \\\\
\text { By }(5)-(4), 6 x&=a+3 \\\\
\text { Substituting } x&=\dfrac{a+3}{6} \\\\
\dfrac{a+3}{6}+z&=a+2 \\\\
z=\dfrac{6 a+12-a-3}{6} &\\\\
z=\dfrac{5 a+9}{6}\hspace{2cm}&\\\\
\end{aligned}$
Since $x, y, z$ are in G.P.,
$\begin{aligned}
&\\
\dfrac{y}{x}&=\dfrac{z}{y} \\\\
x z&=y^{2} \\\\
\dfrac{a+3}{6} \times \dfrac{5 a+9}{6}&=2^{2} \\\\
5 a^{2}+2 y a+27&=144 \\\\
5 a^{2}+2 y a-117&=0 \\\\
(5 a+3 q)(a-3)&=0\\\\
\therefore\ a &=-\dfrac{39}{5} \text { (or) } \\\\
a &=3\\\\
\end{aligned}$
Since $a>0, a=-\dfrac{39}{5}$ is rejected.
$\begin{aligned}
&\\
&\therefore\ a=3
\end{aligned}$
then prove that $(q-r) \log a+(r-p) \log b+(p-q) \log c=0$.
SOLUTION
Let the first term be $A$ and the cominon ratio be $R$ of the given G.P.
$\begin{aligned}
&\\
\therefore u_p &=a \\\\
A R^{\ p-1} &=a \\\\
R^{\ p-1} &=\dfrac{a}{A} \\\\
\log \left(R^{\ p-1}\right) &=\log \left(\dfrac{a}{A}\right) \\\\
(p-1) \log R &=\log a-\log A\\\\
\end{aligned}$
$p-1=\dfrac{\log a-\log A}{\log R} \\\\ $
Similarly,
$\begin{aligned}
&\\
q-1 &=\dfrac{\log b-\log A}{\log R} \\\\
r-1 &=\dfrac{\log c-\log A}{\log R}\\\\
\end{aligned}$
$\begin{aligned}
&(1)-(2) \Rightarrow p-q=\dfrac{\log a-\log b}{\log R} \\\\
&(2)-(3) \Rightarrow g-r=\dfrac{\log b-\log c}{\log R} \\\\
&(3)-(1) \Rightarrow r-p=\dfrac{\log c-\log a}{\log R}\\\\
\end{aligned}$
$\begin{aligned}
\therefore\ & (p-q) \log c =\left(\dfrac{\log a-\log b}{\log R}\right) \log c \\\\
& (q-r) \log a =\left(\dfrac{\log b-\log c}{\log R}\right) \log a \\\\
& (r-p) \log b =\left(\dfrac{\log c-\log a}{\log R}\right) \log b \\\\
\end{aligned}$
$\begin{aligned}
&\text{By } (1)+(2)+(3), \\\\
\therefore\ &(p-q) \log c+(q-r) \log a+(r-p) \log b \\\\
&=\left(\dfrac{\log a-\log b}{\log R}\right) \log c+\left(\dfrac{\log b-\log c}{\log R}\right) \log a+\left(\dfrac{\log c-\log a}{\log R}\right) \log b \\\\
&=\dfrac{\log a \cdot \log c-\log b \cdot \log c+\log a \cdot \log b-\log a \cdot \log c+\log b \cdot \log c-\log a \log b}{\log R} \\\\
&=0
\end{aligned}$
Post a Comment for "Geometric Progression : Problems and Solutions -Part (2)"